2016
DOI: 10.1016/j.jinf.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of extended-spectrum beta-lactamase producing Escherichia coli in community-onset urinary tract infections in France in 2013

Abstract: ESBL-producing isolates were rather frequent in urines in French outpatients in 2013. Males and persons residing in nursing homes were at higher risk of ESBL-positive infection. Despite the increase in ESBL-positive isolates, the susceptibility to antibiotics used to treat cystitis remains high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
18
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 16 publications
(16 reference statements)
7
18
0
13
Order By: Relevance
“…In our study, K. pneumoniae was most frequently detected in urine samples (59.8%). This is not surprising since this pathogen is the second most common cause of community-acquired urinary tract infections developed by Enterobacteriaceae (17). The other samples where K. pneumoniae isolates were reported were blood (11.8%), sputum (8.8%) and DTA (7.8%), and these findings were consistent with the infections caused by this pathogen (10).…”
Section: Two Hundred and Twenty-four P Aeruginosa 79supporting
confidence: 53%
“…In our study, K. pneumoniae was most frequently detected in urine samples (59.8%). This is not surprising since this pathogen is the second most common cause of community-acquired urinary tract infections developed by Enterobacteriaceae (17). The other samples where K. pneumoniae isolates were reported were blood (11.8%), sputum (8.8%) and DTA (7.8%), and these findings were consistent with the infections caused by this pathogen (10).…”
Section: Two Hundred and Twenty-four P Aeruginosa 79supporting
confidence: 53%
“…Community-acquired ESBL K. pneumoniae infection has also emerged. One study from France showed that ESBL-producing strains accounted for 6.6% of community-onset K. pneumoniae urinary tract infections19. It has been recognized that community-based patients can be reservoirs for ESBL- and AmpC β-lactamase-producing strains, especially when they are from nursing home or clinics20.…”
mentioning
confidence: 99%
“…Previous studies have shown several risk factors for ESBL‐producing E. coli community‐acquired UTI; such as older age, previous use of antibiotics, recurrent UTI, previous UTI caused by ESBL‐producing E. coli , female, nursing home residency, nasogastric tube placement and diabetes mellitus . These studies have included asymptomatic bacteriuria, outpatients, cystitis, other Enterobacteriaceae or cases identified through records of clinical microbiology laboratory . In this study, a series of consecutively elderly patients admitted to hospital with community‐onset E. coli UTI is analysed for risk factors for ESBL‐producing E. coli UTI.…”
Section: Discussionmentioning
confidence: 99%
“…20-28 These studies have included asymptomatic bacteriuria, 23,28 outpatients, 21,26,28 cystitis, 27,28 other Enterobacteriaceae 25 or cases identified through records of clinical microbiology laboratory. 22,24,26,28 In this study, a series of consecutively elderly patients admitted to hospital with community-onset E. coli UTI is analysed for risk factors for ESBL-producing E. coli UTI. We found quite a high global percentage of ESBL-producing E. coli UTI (27.3%).…”
mentioning
confidence: 99%